Karakteristik Edible Film Pati Kulit Pisang Uli dengan Penambahan Lilin Lebah(Beeswax) - Rafi Leo Leo Rosi; Raswen Efendi; Farida Hanum Hamzah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Banana uli peel was found to have starch content and yet it has not been optimally utilized. The objective of this research was to study the characteristic of banana uli peel starch edible film after addition with different concentration of beeswax. This research was conducted experimentally by used Complete Randomized Design (CRD) with five treatments and three replications which followed by Duncan’s New Multiple Range Test (DNMRT) at level 5%. Treatments in this research include L0 (without beeswax), L1 (0.2% beeswax), L2 (0.3% beeswax), L3 (0.4% beeswax) and L4 (0.5% beeswax). Characterizations used in this research are test of thickness, solubility, water uptake, water vapor transmission rate, tensile strength, elongation and transparency. The results of variance analysis showed that addition of concentration of beeswax gave significantly affect on thickness, solubility, water uptake, water vapor transmission rate, tensile strength, elongation and transparency. Based on the results of the research, banana uli peel starch edible film L4 (0.5% beeswax) was chosen as the best treatment which has thickness 0.142 mm, solubility 16.34%, water uptake 86.13%, water vapor transmission rate 4.64 g/m2/hour, tensile strength 3.26 MPa, elongation 8.05% and transparency 11.69.Keywords: banana uli peel, beeswax, edible film